2021
DOI: 10.1002/htj.22177
|View full text |Cite
|
Sign up to set email alerts
|

Influence of conjugate heat transfer on the minimization of entropy generation for forced convective flow through parallel plate channel filled with porous material

Abstract: A fluid–solid conjugate heat transfer model is developed to analyze the characteristics of entropy generation for forced convective steady hydrodynamically fully developed laminar flow of a Newtonian fluid through a parallel plate channel filled with porous material by modulating the following parameters: substrate thickness, the ratio of thermal conductivity of wall to fluid, Biot number, the axial temperature gradient in the fluid, and Peclet number. The exteriors of both the walls are subjected to the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The conjugate heat transfer is governed by the conservation of mass and momentum equations in the fluidic domain and the coupled energy conservation equations in both the fluid and solid domain. By neglecting viscous dissipation and radiation heat transfer effects and assuming constant thermo-physical properties for both the solid and fluid, the governing equations are (Borah and Pati, 2021a, 2021b; Faizan et al , 2022):…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The conjugate heat transfer is governed by the conservation of mass and momentum equations in the fluidic domain and the coupled energy conservation equations in both the fluid and solid domain. By neglecting viscous dissipation and radiation heat transfer effects and assuming constant thermo-physical properties for both the solid and fluid, the governing equations are (Borah and Pati, 2021a, 2021b; Faizan et al , 2022):…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Such proposition may hold true when the conductive resistance in the solid wall is negligibly small either due to higher thermal conductivity of the solid substrate or because of negligible thickness of the wall. Nonetheless, in several applications involving internal forced convective flow, the effect of conduction heat transfer in the solid walls may be extremely decisive in dictating the thermal transport characteristics (Borah and Pati, 2021a, 2021b; Faizan et al , 2021). Accordingly, one should analyze the transport phenomena in the fluidic domain and the conductive heat transfer in the solid substrate simultaneously, which is termed as conjugate heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Borah et al 35 investigated the non-uniform heating on conjugate heat transfer in a duct and concluded that heat transfer rate decreases with the increase in the amplitude of sinusoidal non-uniform heating. Borah and Pati 36 worked on conjugate heat transfer filled with porous medium and found that the thermal conductivity of the solid wall also plays a decisive role for entropy generation. Borah et al 37 investigated the non-uniform asymmetric heating on conjugate heat transfer in a microchannel and concluded that asymmetric heating has more influence than nonuniform heating.…”
Section: Introductionmentioning
confidence: 99%